2023
DOI: 10.3390/jcm12237489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multidisciplinary Biopsychosocial Rehabilitation on Short-Term Pain and Disability in Chronic Low Back Pain: A Systematic Review with Network Meta-Analysis

Ivan Jurak,
Kristina Delaš,
Lana Erjavec
et al.

Abstract: Chronic low back pain (CLBP) is a significant public health issue, with prevalence intensifying due to an ageing global population, amassing approximately 619 million cases in 2020 and projected to escalate to 843 million by 2050. In this study, we analyzed the effects of multidisciplinary biopsychosocial rehabilitation (MBR) on pain and disability. To address this question, we conducted a PRISMA-guided systematic review and random-effect network meta-analysis on studies collected from six electronic databases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…This comprehensive FBSS care pathway can help improve decision-making, minimize practice variation, and optimize outcomes. However, the implementation of multidisciplinary care is frequently hindered by limited access to specialized centers and higher costs owing to the involvement of multiple professionals [ 98 ].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…This comprehensive FBSS care pathway can help improve decision-making, minimize practice variation, and optimize outcomes. However, the implementation of multidisciplinary care is frequently hindered by limited access to specialized centers and higher costs owing to the involvement of multiple professionals [ 98 ].…”
Section: Managementmentioning
confidence: 99%
“…However, a network meta-analysis indicated that MBR demonstrates only minimal differences in effectiveness when compared to minimal intervention and usual care in the treatment of chronic LBP, with no single treatment approach exhibiting clear superiority. Therefore, a thorough cost-benefit analysis is warranted to determine the most economically viable and clinically effective treatment modality among multidisciplinary approaches [ 98 ].…”
Section: Managementmentioning
confidence: 99%